Classroom Response Systems in the Wild: Technical and Non-Technical Observations - Vetterick, Jonas; Garbe, Martin; Dähn, Andreas; Cap, Clemens H. (International Journal of Interactive Mobile Technologies (iJIM), 2014)
Classroom Response Systems (CRS) provide lecturers a communication channel to get feedback from their students. In lessons with large audiences, CRS allow students to ask questions or state issues as the lesson continues. During the development and usage of our new CRS "Tweedback", we observed several technical and non-technical problems, which are likely to be general CRS issues. Observed problems are caused by necessary devices, their connectivity and lecturersâ?? and studentsâ?? different ways to use CRS. In this paper, we describe our observations of technical and nontechnical problems and suggest solutions, which may be applied generically to interactive feedback systems.